2019
DOI: 10.1590/0034-7167-2018-0356
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pressure injury in an oncological intensive care unit

Abstract: Objective: to investigate the incidence of pressure injury in cancer patients of an intensive care unit. Method: A longitudinal study with 105 patients admitted to an oncological intensive care unit. The incidence rate was calculated as the number of events per 100 patient-days. Cumulative incidence was calculated both globally and according to selected characteristics, and submitted to hypothesis tests. Results: incidence rate per 100 patient-days was 1.32, and global cumulative incidence was 29.5%. A highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
1
18
1
12
Order By: Relevance
“…In this study, the incidence rate of PI per 100 patient-days in critically ill patients with cancer was 3.14%, and the cumulative incidence rate was 3.09%. Our results are quite different from the results of Jomar et al in Brazil, who reported a patient-day incidence rate of PI in oncological ICU patients of 1.32%, and a cumulative incidence rate of 29.50% [ 12 ]. A PubMed, Web of Science, and Google Scholar search by the present authors did not produce relevant reports on the incidence of PI in critically ill patients with cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the incidence rate of PI per 100 patient-days in critically ill patients with cancer was 3.14%, and the cumulative incidence rate was 3.09%. Our results are quite different from the results of Jomar et al in Brazil, who reported a patient-day incidence rate of PI in oncological ICU patients of 1.32%, and a cumulative incidence rate of 29.50% [ 12 ]. A PubMed, Web of Science, and Google Scholar search by the present authors did not produce relevant reports on the incidence of PI in critically ill patients with cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…However, 76% of patients with cancer had PI during hospitalization [ 11 ]. Longitudinal study results of the PI incidence rate of patients in oncological ICU showed that the incidence rate per 100 patient-days is 1.32%, and the cumulative incidence rate is 29.5%; moreover, it showed that the incidence of PI is higher in critically ill patients with cancer who had at least 1 episode of diarrhea, received enteral nutrition, and took vasoactive or sedative drugs for an extended period of time [ 12 ]. At present, PI risk prediction is mainly evaluated by the Waterlow PI risk assessment form and Braden scale for PI risk, but the evaluation content of these assessments is limited, and nursing practice data showed that the results of these assessments need to be combined with an overall evaluation of clinical data to provide more accurate risk prediction [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidência e fatores relacionados ao aparecimento de lesões por pressão em unidade de terapia intensiva Quando observados os valores atribuídos na avaliação de risco para o desenvolvimento de LP por meio da escala de Braden nos participantes com e sem lesão, nota-se que nenhum paciente sem lesão apresentou risco muito alto (6)(7)(8)(9). A maior parte do grupo com lesão apresentou porcentagem de 62,5 % para alto risco (10-12), 25% para risco moderado (13)(14), 12,5% para baixo risco (15)(16)(17)(18) e nenhum paciente teve escore de risco maior ou igual a 19 (Tabela 4). 18 .…”
Section: Métodounclassified
“…A maior parte do grupo com lesão apresentou porcentagem de 62,5 % para alto risco (10-12), 25% para risco moderado (13)(14), 12,5% para baixo risco (15)(16)(17)(18) e nenhum paciente teve escore de risco maior ou igual a 19 (Tabela 4). 18 .…”
Section: Métodounclassified
See 1 more Smart Citation